World Commodity Prices, Job Security and Health: Evidence from the Mining Industry - David W. Johnston; Michael A. Shields; Agne Suziedelyte (Institute of Labor Economics (IZA), 2017)
A lack of job security is an increasingly prevalent characteristic of modern labour markets, and there is evidence that recent financial crises have exacerbated this issue. In this paper, we assess how exogenous changes in the macroeconomic environment affect workers' perceived job security, and the impact of job security on measures of mental and physical health. To identify these effects, we exploit variation in world commodity prices over the period 2001–15, and analyse 15 waves of individual-level panel data that includes unusually detailed classifications of mining workers. We find that commodity price movements drive changes in perceived job security, which in turn significantly and substantively affects the mental health of workers. In contrast, we find no effects on physical health. Our results imply that the estimated welfare costs of recessions are substantially larger when the effects of job insecurity on the health of workers is considered.
Keywords: J11; J21; I31; 330; job security; health; macroeconomic conditions; panel data